1999
DOI: 10.1248/bpb.22.1366
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Gastrointestinal Transit and Motility in Dogs with Postoperative Ileus.

Abstract: We investigated the relationship between gastrointestinal (GI) transit and motility during postoperative ileus in dogs undergoing a single laparotomy. We combined X-ray radiography for a GI transit study with chronically implanted force transducers (FTs) for a GI motility study. Radio-opaque markers made of polyethylene and steel wires or barium sulfate were used to examine solid substance transit or liquid substance transit. For a while after the end of the operation, postoperative ileus was observed, with we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…19 Phase-III-like contractions first appeared in the ileum, followed by the jejunum, duodenum, and finally in the stomach; this pattern of recovery of interdigestive motility matched that of a previous report. 19 Moreover, phase-III-like activity in all regions of the small intestine and stomach recovered earlier postoperatively after epidural morphine. However, the postoperative IMC recorded by means of a multipressure sensor probe placed intraoperatively into the jejunum did not correlate with the first passage of flatus and stool.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…19 Phase-III-like contractions first appeared in the ileum, followed by the jejunum, duodenum, and finally in the stomach; this pattern of recovery of interdigestive motility matched that of a previous report. 19 Moreover, phase-III-like activity in all regions of the small intestine and stomach recovered earlier postoperatively after epidural morphine. However, the postoperative IMC recorded by means of a multipressure sensor probe placed intraoperatively into the jejunum did not correlate with the first passage of flatus and stool.…”
Section: Discussionsupporting
confidence: 89%
“…[16][17][18] In particular, a previous report proved that the appearance of IMCs in the stomach (gastric IMCs or GIMCs) was correlated with both gastric emptying and small intestinal transit time. 19 The present study examined the effects of epidural analgesia on gut motility in an SGT dog model using epidural administration of saline, morphine, or ropivacaine, and compared these results with continuous intravenous injection of low-dose morphine.…”
Section: Introductionmentioning
confidence: 99%
“…Reflecting intestinal paralysis, IMCs disappear during abnormal conditions such as open abdominal surgery. A previous report demonstrated that the appearance of IMC in the stomach (gastric IMC) correlated with the recovery of digestive transport (Tsukamoto et al, 1999;Shibata et al, 2002;Tanaka et al, 2004).…”
Section: Gastrointestinal Motility Patterns With Sgtmentioning
confidence: 94%
“…Eventually phase III-like contractions appear first in the ileum, followed by the jejunum, duodenum, and finally in the stomach (Tsukamoto et al, 1999;Nakayoshi et al, 2007).…”
Section: Gastrointestinal Motility Patterns After Open Abdominal Surgerymentioning
confidence: 99%
See 1 more Smart Citation